UV-Vis Spectroscopic Analysis for Band Gap Determination of Cobalt-Doped Magnetite (Fe2.5Co0.5O4) Nanoparticles Derived from Natural Iron Sand - Saputra, Kormil; Inayah, Rahmatun; Aminy, Ika Umratul Asni; Ardianto, Teguh; Kurniawidi, Dian Wijaya (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2025)
Doping is an effective approach to altering the electronic and structural properties of a material, thereby influencing its optical and magnetic characteristics. This study successfully synthesized and characterized cobalt-doped magnetite (Fe2.5Co0.5O4) nanoparticles from natural iron sand using the coprecipitation method. The main objective was to evaluate the optical properties of the synthesized material through UV-Vis spectral analysis and to compare the band gap energy values using three approaches: the Tauc method (direct and indirect transitions), the Kubelka–Munk method, and the Urbach energy calculation as an indicator of structural disorder. The characterization results revealed that the incorporation of Co2+ ions into the magnetite structure induced significant changes in the absorption patterns, including the emergence of new absorption peaks and a redshift in wavelength. The obtained band gap values were 3.71 eV (Tauc-direct), 2.18 eV (Tauc-indirect), and 2.33 eV (Kubelka–Munk), confirming the presence of two types of optical transitions. Furthermore, the relatively low Urbach energy (0.07138 eV) indicated that the crystal structure remained well-preserved despite the modifications induced by doping. This study highlights the importance of employing multi-method approaches for reliable optical characterization and demonstrates that Fe2.5Co0.5O4 materials derived from local resources possess promising potential for photocatalytic and optoelectronic applications.